Meningkatkan Wawasan Kebangsaan Melalui Pengenalan Warisan Budaya dan Permainan Tradisional Jawa Tengah di Sanggar Bimbingan Sungai Mulia 5 Kuala Lumpur-Malaysia: Enhancing National Awareness Through the Introduction of Central Javanese Cultural Heritage and Traditional Games in Sungai Mulia 5 Kuala Lumpur-Malaysia - Aprilia, Rennanti Lunnadiyah; Satibi, Imam; Hermawan, Risdianto; Maemunah, Titi; Priyanto, Eko; Sukawi, Zaenal; Irianto, Heru; Khoiri, Ahmad; Affandi, Achmad; Sejati, Hono; Handriani, Eka; Sutomo, Sutomo; Legowo, Yogi Ageng Sri; Hafni, Nurlaili Dina (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
In the era of globalization, national identity poses a unique challenge, particularly for Indonesian diaspora children living far from their homeland. The children at Sanggar Bimbingan Sungai Mulia 5 (SB SM 5) in Kuala Lumpur, Malaysia, are mostly migrant children growing up in environments with minimal exposure to Indonesian culture. This condition risks weakening their emotional connection to national identity and the cultural heritage of Nusantara. This international community service program aims to enhance the national awareness of children aged 10–14 years at SB SM 5 by introducing the cultural heritage of Borobudur Temple as a symbol of national civilization and traditional Javanese games such as cublak-cublak suweng. The methods used include participatory approaches, edutainment, and experiential learning, designed to create an interactive and enjoyable learning experience. The children participated in activities such as visual presentations, storytelling, hands-on traditional games, and reflections on national values. The results demonstrated an increase in knowledge about Borobudur from 10% to 90% and a high level of enthusiasm for traditional games. The children not only gained an understanding of Indonesian culture but also felt a sense of pride and emotional closeness to their homeland. As a follow-up, plans include the development of digital modules, regular cultural classes, and collaboration with diaspora communities to ensure the sustainability of this program. This initiative successfully established an emotional connection between diaspora children and Indonesia's cultural identity, making it a model applicable to other diaspora communities